Application of biohybrid membranes for arsenic and chromium removal and their impact on pollutant accumulation in soybean (Glycine max L.) seedlings - Bogino, Sofía (2024)
Chromium and arsenic are among the priority pollutants to be controlled by regulatory and health agencies due to their ability to accumulate in food chains and the harmful effects on health resulting from the ingestion of food contaminated with metals and metalloids. In the present work, four biohybrid membrane systems were developed as alternatives for the removal of these pollutants, three based on polyvinyl alcohol polymeric mesh (PVA, PVA-magnetite, PVA L-cysteine) and one based on polybutylene adipate terephthalate (PBAT), all associated with bioremediation agents. The efficiency of the bioassociation process was assessed through count methods and microscopy. The removal capacity of these systems was evaluated in synthetic liquid medium, both in the absence and in the presence of soybean (Glycine max L.) seedlings. The content of chromium and arsenic was also analyzed in aerial and hypogeous tissues of seedlings grown on contaminated solid substrate. PVA and PVA-magnetite biohybrid membranes showed the highest removal rates, between 57 and 75% of the initial arsenic content and more than 80% of the initial chromium content after 48 h of treatment, when evaluated in synthetic liquid media with initial concentrations of 2.5 ppm of pentavalent arsenic and 5 ppm of hexavalent chromium, both in presence and absence of seedlings. PVA and PBAT promoted a significant reduction of arsenic translocation to the aerial parts, generally edible, of this crop of agronomic interest. The systems tested showed a high potential for biotechnological applications in matrices affected by the presence of arsenic and chromium.